French Adaptation and Validation of the Expanded Version of the Three-Factor Levenson Self-Report Psychopathy Scale. (October 2020) - Maheux-Caron, Véronique; Gamache, Dominick; Sellbom, Martin; Christian, Elliott; Lussier, Yvan; Savard, Claudia
The goal of this study ( N = 432 participants from a community sample) is to report on the psychometric properties of a French adaptation of the Expanded Version of the Three-Factor Levenson Self-Report Psychopathy Scale (E-LSRP), which was developed to alleviate some shortcomings of the original LSRP. A three correlated factor exploratory structural equation modeling model showed the best fits and attained satisfactory indices. There were significant, conceptually meaningful associations with measures of Dark Triad traits, pathological narcissism, empathy, impulsivity, substance misuse, and social desirability. Incremental validity over a 19-item scale proposed by Brinkley et al. was also mostly demonstrated, especially for convergent validity. Overall, the French E-LSRP possesses sound psychometric properties, comparable for the most part with the original instrument, and should be seen as a useful measure of psychopathic traits in community samples.